Towards a fiscal responsibility regime in Nigeria : the civil society-legislature nexus 2006 - Civil Society Legislative Advocacy Centre; United States Agency for International Development (USAID) (Abuja, Nigeria : Civil Society Legislative Advocacy Centre (CISLAC), 2006)
A collaboration of the civil society groups and the legislature in a face-to-face deliberation to brainstorm on how best they can make the Fiscal Responsibility Bill 2006 work.
oif 19/09/2018
Loans
Keywords: Fiscal policy; Nigeria